2010
DOI: 10.1097/mcp.0b013e3283328398
|View full text |Cite
|
Sign up to set email alerts
|

Biologic therapies for asthma

Abstract: Biologic therapies currently represent useful adjunctive treatments for asthma, especially in patients with more severe disease that is not responsive to conventional therapies alone. However, the varied responses now found suggest that specific phenotypes may need to be identified to see optimal effects from specific treatments. Further studies are required to access the efficacy and side effect profiles of these therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…Steroid agents used to treat asthma have side effects when administered in high concentrations over long periods of time, and compliance with inhalers remains an important therapeutic issue. While biologic therapies show potential (42), they too have side effects and are costly. Data presented in this study indicate that treatment with a new type of immunomodulator, the GABA A R agonist HNK, modulated inflammation associated with asthma at a dose that was well tolerated with multiple injections over the course of several weeks in a well-studied model of allergic airway inflammation, and which falls within pharmacokinetic range (43).…”
Section: Discussionmentioning
confidence: 99%
“…Steroid agents used to treat asthma have side effects when administered in high concentrations over long periods of time, and compliance with inhalers remains an important therapeutic issue. While biologic therapies show potential (42), they too have side effects and are costly. Data presented in this study indicate that treatment with a new type of immunomodulator, the GABA A R agonist HNK, modulated inflammation associated with asthma at a dose that was well tolerated with multiple injections over the course of several weeks in a well-studied model of allergic airway inflammation, and which falls within pharmacokinetic range (43).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a clinical trial in which mepolizumab was given to patients with asthma for 6 months showed reduced exacerbation frequency and steroid requirements [104,105]. Gruenberg and Busse's study [106] suggested that patients who are being treated with steroid therapy and continue to have persistent sputum eosinophilia may benefit from an agent that can specifically target and reduce eosinophils. Clinical trials with other anti IL-5 antibodies, including reslizumab and enralizumab, are currently in progress.…”
Section: Recent Treatment Strategies For Airway Remodelingmentioning
confidence: 99%
“…Clinically, TNF-α has been proposed as a target for asthma therapy: in patients with severe asthma, elevated levels of TNF-α in bronchoalveolar lavage (BAL) fluid have been reported [25]. Antibodies targeting TNF-α, as well as a fusion protein of the type II TNF receptor with the Fc region of human IgG, are the therapeutics that have been used in clinical trials for treatment of asthma.…”
Section: Asm-mediated Modulation Of Inflammationmentioning
confidence: 99%